A switched optimal control approach to reduce transferring time, energy consumption, and residual vibration of payload's skew rotation in crane systems. (March 2019) - Ho, Tho; Suzuki, Kensuke; Tsume, Mitsuo; Tasaki, Ryosuke; Miyoshi, Takanori; Terashima, Kazuhiko
Abstract: In this paper, nonlinear optimal control schemes are proposed to reduce transferring time, energy consumption, and residual vibration for the payload's skew rotation process of crane systems. The main contribution of this paper is to reduce the energy consumption without trading-off the sub-optimal transferring time. The novel idea is to use an electro-mechanical clutch to intelligently disengage the connection between the motor and the payload during the motion such that the payload can continue rotating only by its own momentum. As a result, a switched optimal control problem must be realized. Two solutions, namely particular and general schemes are proposed in the paper, where physical constraints of the actuator including bounded velocity and bounded acceleration are explicitly taken into account. Both simulation and experimental results are provided to prove the effectiveness of the proposed optimal control systems. The established schemes can be directly applied to transfer the payload to a desirable skew orientation without any residual oscillation, or can be utilized as a sub-optimal-time reference trajectory planner of the skewing control module in either overhead or rotary crane systems. Furthermore, the hybrid rotation process presented in this paper, which is driven by the engaging/disengaging event of the clutch, can be served as a theoretical benchmark for any newly established switched optimal control method. Highlights: On/Off events of a clutch result in a switched skew rotation dynamic of the payload. Hybrid dynamic of the payload' skew rotation is formulated and verified. Optimal controls are presented to achieve a fast skew transfer without vibration. Switched optimal control is proposed to save energy without trading-off transfer time. Effectiveness of proposed schemes are verified by both simulations and experiments.